Final review draft: WIRED GHG accounting working group report - Unidentified author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2020)
This paper sets forth principles and design elements for consideration by policymakers for the development of accounting and compliance frameworks for electricity sector programs.
WIRED GHG accounting working group report
In early 2020, the Center for the New Energy Economy (CNEE), at the request of the Western Energy Industry Leaders (WEIL), convened a group of Western governors' energy advisors along with a small but diverse group of experts representing utilities, power marketing administrations, renewable energy companies and clean energy advocates, collectively referred to as the "Western Interconnection Regional Electricity Dialogue" (WIRED). The goal of this effort is to provide a set of recommendations to governors by the end of the year. To achieve this goal, CNEE has facilitated a series of work group meetings to discuss and analyze a range of regional electricity issues including resource adequacy (RA), state clean energy and climate policies, and transmission development.
Keywords: Western Interconnect Regional Electricity Dialogue (WIRED); Clean energy; Clean energy -- Accounting; Clean energy -- Compliance; Electric power production; Electric power distribution